2022
DOI: 10.12669/pjms.38.4.4797
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic importance of bone marrow aspiration evaluation: A single-center study

Abstract: Background &Objective: Early diagnosis can be made based on the morphological examination of bone marrow aspiration (BMA) until the bone marrow biopsy (BMB) result is reported. This allows for treatment to be started immediately, especially in hematological malignancies for which urgent treatment is indicated. This study aimed to determine the sensitivity and importance of bone marrow aspiration in the diagnosis of hematological malignancies. Methods: In this study, the data of patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Similar to our study, Dogan et al also found leukemia to be the most common haematological malignancy while metastatic deposits being the least common. 1 Acute leukemias with 137 (54.8%) cases were more common as compared to chronic leukemias with 57 (22.8%) cases. Similar findings were also observed by Khan et al in their study in which majority of cases were acute leukemias.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Similar to our study, Dogan et al also found leukemia to be the most common haematological malignancy while metastatic deposits being the least common. 1 Acute leukemias with 137 (54.8%) cases were more common as compared to chronic leukemias with 57 (22.8%) cases. Similar findings were also observed by Khan et al in their study in which majority of cases were acute leukemias.…”
Section: Discussionmentioning
confidence: 95%
“…3 Dogan et al also found similar results in their study. 1 Among myeloproliferative disorders except CML, out of 6 cases of essential thrombocythemia, simultaneous BMA and BMB was done in 3 cases which showed 100% concordance. Of the two cases of polycythemia vera, one case showed myelofibrosis on trephine section and had dry tap marrow aspirate thereby emphasising the role of BMB to assess overall cellularity and degree of fibrosis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations